Students’ Conceptual Understanding And Difficulties On Static Fluids: A Literature Review - Irawan, Ivan Danar Aditya; Khusaini, Khusaini; Islamiyah, Muizzatul; Basri, Nur Akhyar; Ardilla, Sarah Lutfiah (Jurnal Phi: Kurnal Pendidikan Fisika & Terapan, 2026)
The research is a literature study that aims to explain students' concept understanding and difficulties in Static Fluid material. The research method uses descriptive qualitative by analyzing Sinta/international conference/Scopus accredited journals. The analysis was conducted on the concepts of hydrostatic pressure, Archimedes' law and Pascal's law. The articles used were 9 articles published between 2019-2023. The results of the analysis show that most of the studies show that the understanding of the concepts in static fluid material is rather low. There are many difficulties experienced by students on the concepts of hydrostatic pressure, Archimedes' law and Pascal's law. Various efforts to improve and overcome the difficulties include the application of guided inquiry learning models, CCBL models, formative assessment in collaborative inquiry learning, and STEM-integrated experimental learning with formative assessment. The profile of understanding and difficulties can be used by teachers as a basis for designing solutions to create more effective learning and designing research to overcome difficulties.